LASER MODIFICATION OF BASALT TEXTILE MATERIALS FOR FUNCTIONAL APPLICATIONS IN LIGHT INDUSTRY - Markevich, Maria Ivanovna; Asanov, Dauranbek Jadigerovich (SCIENCE and SOCIETY, 2026)
The article The effect of laser radiation on basalt fabric TBK-100 was investigated in order to develop regimes for its controlled modification. The treatment was carried out at energy inputs of 60-240 J with a fixed exposure time. The surface morphology and elemental composition of the samples before and after laser treatment were studied using scanning electron microscopy and energy-dispersive microanalysis. It was established that when the threshold energy input is exceeded, intensive melting of the fibers occurs with the formation of through holes with a diameter of about 450 µm; the damage mechanism is of a thermophysical nature. The obtained results demonstrate the prospects of laser perforation of basalt fabrics for producing functional materials with controlled permeability.